Identifikasi Pela Gandong Dalam Merilis Hubungan Kekerabatan - Dyastuti, Risqi Mumpuni (BAMETI Customary Law Review, 2024)
Cultural diversity in a society triggers conflict. Conflict resolution due to primordialism is needed in order to achieve a peaceful and prosperous society. The legal consequences of a conflict, as well as the inability of an indigenous community can lead to legal relations that are expected to strengthen unity. So it is necessary to identify existing cultural relations accompanied by kinship relations between communities as a guide in social life. The purpose of this article is to find out the culture in the community as a conflict resolution and the form of legal relations from the community due to a legal act that still upholds culture in order to achieve unity. The method used is normative juridical, diagnostic with document studies. The data used is public secondary data. The data collection method used is using the method of uninvolved observation. The results show that pela-gandong can be used as a conflict resolution, used as a tool for poverty reduction and causes kinship relations between people who do not have the same blood background or descent and establish a cooperative relationship that helps each other until next generation.